Electrocatalytic hydrogenation of benzoic acids in a proton-exchange membrane reactor. Issue 34 (17th August 2021) - Fukazawa, Atsushi; Shimizu, Yugo; Shida, Naoki; Atobe, Mahito
Abstract : The highly efficient chemoselective hydrogenation of benzoic acids to cyclohexanecarboxylic acids was carried out in a proton-exchange membrane reactor under mild conditions without hydrogenation of the carboxyl group. Abstract : The highly efficient chemoselective electrocatalytic hydrogenation of benzoic acids (BAs) to cyclohexanecarboxylic acids (CCAs) was carried out in a proton-exchange membrane reactor under mild conditions without hydrogenation of the carboxyl group. Among the investigated catalysts, the PtRu alloy catalyst was found to be the most suitable for achieving high current efficiencies for production of CCAs. An electrochemical spillover mechanism on the PtRu alloy catalyst was also proposed.